Senegal : Staff Report for the 2014 Article IV Consultation and Eighth Review Under the Policy Support Instrument. (IMF Staff Country Reports; Country Report ;, 2015)
EXECUTIVE SUMMARY Article IV issues. The government is committed to implementing the 'Plan Senegal Emergent' (PSE), which contains valid diagnostics and policies to boost growth and accelerate poverty reduction. GDP growth is projected to rise from less than 4 percent in recent years to 4.5 percent in 2014. Inflation remains low. Growth can potentially reach 7 percent by 2019 if PSE- related reforms are consistently and rapidly implemented. The authorities believe this growth rate will be achieved two years earlier. The impact of Ebola on growth will be limited in 2014 but can become substantial in 2015 should the epidemic spread in the region. Fiscal stance. The fiscal outlook has improved owing to stronger revenue performance and expenditure control, and the overall deficit is expected to fall to about 5 percent of GDP in 2014. The 2015 budget targets a further reduction in the deficit to 4.7 percent of GDP, less ambitious than the 4.0 percent of GDP recommended by staff. However, the authorities expect to limit the deficit close to the level recommended by staff by holding back appropriations for new public investment projects until feasibility studies are ready. Staff and authorities agreed that Ebola-related shocks could add 0.3 percent of GDP to the deficit in 2015. The authorities remain committed to bringing the fiscal deficit in line with the WAEMU target of 3 percent of GDP in the medium term. Structural reforms. The PSE offers an achievable development strategy, including the right mix of private investment to be crowded in by public investment in both human capital and infrastructure. However, unlocking private investment, including FDI, requires speeding up reforms to the business climate and improving public sector governance. Frontloading public investment without implementing the necessary structural reforms may jeopardize fiscal targets and debt sustainability while failing to raise growth from its sub-par trend. Program implementation. Performance under the PSI-supported program has been satisfactory with end-June 2014 program targets met except for a minor breach of the non- concessional borrowing ceiling due to weak debt management. This borrowing does not materially affect debt sustainability, and debt management weaknesses are being addressed. Staff recommends completion of the eighth PSI review and proposes a waiver of nonobservance of the assessment criterion on non-concessional borrowing.